(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Influence of Indian philosophy on Herman Hesse and elements of autobiography in Siddhartha. The novel reflects Hesse’s preoccupation with India at a time of personal crisis and his search for complete freedom which he could not find in his Occidental sensibilities which he found too intellectual and far from reality. Hesse’sfinal conclusion on religion and his idea of enlightenment are beautifully assimilated in this masterpiece which is widely read in American curriculum. The article looks at Hesse’s life and events which propelled him to write Siddhartha and his own view which finds voice in his protagonist Siddhartha. The novel in many ways is autobiographical and analysis the inner struggle of a man brought up in a comfortable house but takes up individualistic path to find salvation